Analysis Of The Effect Of Hyperbarics On Reducing Blood Sugar And Wound Healing Phase In DM Patients : Systematic Review - Wiratama, Rahardyan Dika; Abdul Muhith; Hotimah Masdan Salim; Siti Nur Hasina (Journal for Quality in Public Health, 2024)
Diabetes Mellitus (DM) ranks fifth as a cause of death, Diabetes Mellitus (DM) is a deadly disease after coronary disease, stroke, cardiovascular contamination disease, and respiratory disease. Diabetes Mellitus is an infectious disease that proliferates continuously, usually the side effects are not distinguished because the side effects appear mild such as weakness, wounds that do not heal, and polyuria. The purpose of this study was to determine the effect of hyperbaric on blood sugar reduction and wound healing phase of DM patients. The method used in this study is systematic review with systematic review (PRISMA) using several journal databases from Google Scholar, Science Direct, and Pubmed from 2019-2024 with the keywords "Diabetes Mellitus", "Hyperbaric", "Decrease in blood sugar levels ”, “wound healing phase of DM patients”. 10 articles were ready to be reviewed 10 articles were obtained with PRISMA. The results of the systematic review study showed that there was an effect of hyperbaric administration on reducing blood sugar levels and the wound healing phase of patients with DM. It is hoped that hyperbaric therapy will prevent complications from DM disease.